Taxiing maneuvers dynamics and control - Marcio Caetano Turbuk (2009)
Airport ground operations are becoming very complex due to the increasing of flight numbers along the years. New automation scenarios are demanded to support ground operations, with automatic trajectory generation and tracking by the aircraft. This work intends to provide an initial approach to aircraft ground modeling, providing a five degree of freedom model, presenting most of efforts that occurs on ground operations. Besides modeling a trajectory generator was developed to create the path to be followed by the aircraft, providing time variant references for position, orientation and velocity. As final approach, a control law was designed, taking into account the desired positioning, orientation and speed at each time.